Differential efficacies of marigold leaves and turmeric paste on the healing of the incised wound in sheep (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study was undertaken to compare the curative efficacy of marigold leaf paste and turmeric paste on healing the incised wound in sheep. The study also determined the antimicrobial effects and histopathological changes in a wound’s healing process treated with these medicinal herbs.  Materials and Methods: Surgical wounds (n = 18) were created aseptically in the skin of the flank region of six healthy sheep dividing them into three experimental groups. Follow-up data were taken up to day 21. Different morphological characteristics of the wound and wound contraction (length and width) were recorded weekly. Samples were collected on days 1, 2, and 3 to test the antimicrobial effects and on days 1, 3, and 7 for histopathological studies.  Results: Treatment with marigold leaf paste and turmeric paste resulted in a swelled wound area of 11.78 ± 0.38 mm and 11.52 ± 0.27 mm, respectively. The wound areas were comparatively lower than that of the control group (11.44 ± 0.20 mm). Moreover, the least elevation (2.44 ± 0.12 mm) of the sutured line from the skin surface was noted and compared between the marigold leaf paste and normal saline (2.74 ± 0.13 mm). Bacterial colonies in the nutrient agar medium cultured with swabs from the normal saline-treated group’s wound area were found on day 1. On the contrary, bacterial colonies were absent on days 2 and 3 of treatment in the groups treated with both the paste of marigold leaves and turmeric. Less intense tissue reactions and higher keratinization of epithelium were shown in the group treated with marigold leaf paste than turmeric paste and saline-treated groups.  Conclusion: Marigold leaf paste showed less tissue reaction and healed the wounds effectively. Thus, this paste could be used for the treatment of superficial wounds in sheep.J. Adv. Vet. Anim. Res., 7(4): 750-757, Dec 2020http://doi.org/10.5455/javar.2020.g477